Developing country interests in agricultural reforms under the World Trade Organization - Diao, Xinshen; Roe, Terry L.; Somwaru, Agapi (International Food Policy Research Institute, 2002)
The gains to developing countries from agricultural reform in developed countries is found to benefit most, even the net food importers, although the gains vary depending on a country’s trade pattern. This results because the agricultural policy of a small number of developed countries cause the major distortions in world markets, and developing countries whose major share of agricultural trade is with the E.U. are impacted quite differently than those trading with the U.S. Even though Japan and Korea maintain high trade barriers, these barriers are found to have small effects on developing countries. The long-run benefits of reform are found to greatly exceed the short-run gains.